Competent in evidence‐based practice (EBP): validation of a measurement tool that measures EBP self‐efficacy and task value in speech–language therapy students. Issue 4 (13th April 2013) - Spek, B.; Wieringa‐de Waard, M.; Lucas, C.; van, N.
Abstract Background Worldwide speech–language therapy (SLT) students are educated in evidence‐based practice (EBP). For students to use EBP in their future day‐to‐day clinical practice, they must value EBP as positive and must feel confident in using it. For curricula developers it is therefore important to know the impact their teaching has on these aspects of students' motivational beliefs. Aims To develop and validate a measurement tool to assess EBP task value and self‐efficacy in SLT students. Methods & Procedures A 20‐item questionnaire was developed based on a review of the literature and an additional group interview with speech–language therapists. Face validity of the questionnaire was established using a Delphi panel consisting of six EBP lecturers. Dutch bachelor SLT students (n = 149) with a different level of EBP knowledge and skills filled in the newly developed questionnaire. Reliability (internal consistency) was assessed using Cronbach's alpha and internal validity using a principal component analysis (PCA). Construct validity was assessed by comparing the bachelor SLT student scores with a group of m students (n = 15) who were highly experienced in EBP. Outcomes & Results The PCA showed that the questionnaire consists of two components, representing EBP task value and self‐efficacy, both with good reliability (Cronbach's α = 0.83 and 0.79, respectively). The hypothesis that master's students would score significantly higher on both components than bachelor SLT students was met. Conclusions & Implications The study provides evidence on the internal consistency and construct validity of this questionnaire to evaluate EBP task value and self‐efficacy in SLT students. As is common with new measures, more research is needed to evaluate further its psychometric properties.